The Role of Investment, Tourism Industry and Tourist Visits in Improving the Tourism Sector in Indonesia - Muhamad Syahiddin; Sumaryoto , Sumaryoto; Yolanda , Yolanda (Jurnal Multidisiplin Indonesia, 2025)
This study looks at how investment, the travel and tourism sector, and visitor numbers affect Indonesia's tourism business. Panel data comprising 41 districts/cities in the provinces of West Java, Yogyakarta, and Bali from 2014 to 2023 is analyzed using the Pooled Least Squares approach. The fixed effect model used to ascertain the impact of investment, the tourism industry, and tourist visits on Indonesia's tourism sector is displayed via linear regression analysis of panel data. The study's findings show that traditional hotels currently get the majority of investments in the tourism sector, while sustainable tourism wants environmentally friendly hotels and expects environmentally friendly tourism practices and regenerative concepts. The tourism sector in Indonesia needs to improve the quality of infrastructure, information technology, and non-leisure resources. Utilizing the wealth of natural resources, setting new standards for tourism excellence, contributing to economic growth, as well as preserving Indonesia's natural and cultural heritage are strategies that can be carried out to attract a lot of investment aimed at addressing the gap in tourism infrastructure.